Photosynthesis, mixotrophy and microbial plankton dynamics in two high Arctic lakes during summer - Laybourn-Parry, J; Marshall, WA (2003)
Photosynthesis and microbial plankton dynamics of two lakes in the Kongsfjorden catchment of Spitzbergen (Svalbard Archipelago, 78°N) were investigated during the summer of 2000. One of the lakes (Tvillingvatnet) served as the water supply for the village of Ny Ålesund. The other was a deeper, larger unnamed lake in the Ossian Sarsfjella reserve - named Lake OS in this study. Both lakes can be classified as oligotrophic on the basis of chlorophyll a and inorganic nutrient concentrations. Chlorophyll a concentrations ranged between 0.33 and 1.65 μg l-1 in Tvillingvatnet and 0.2 and 0.3 μg l-1 in Lake OS. The phytoplankton was dominated by chrysophytes and cryptophytes, with the diatom Rhizosolenia and a number of dinoflagellate species. Rates of photosynthesis were typically low, between 24.5 μg and 1.0 mg l-1 day -1 in Tvillingvatnet (photosynthetic efficiency 0.004-0.26), and between 3.1 and 29.5 μg l-1 day -1 in Lake OS (photosynthetic efficiency 0.0019-0.0085). Among the phytoflagellates (PNAN) there were a number of mixotrophs which reached their peaks of abundance before other PNAN. Mixotrophy appeared to provide a competitive advantage. Grazing rates for the mixotroph Dinobryon ranged between 0.063 and 1.12 pg C cell -1 day-1 in Lake OS and between 0.22 and 1.11 pg cell -1 day-1 in Tvillingvatnet, with rates increasing between July and August. However, Dinobryon removed less than 1% of bacterial biomass day-1, while the heterotrophic nanoflagellates (HNAN) removed up to 28% of bacterial biomass day-1. Bacterial concentrations were low, with a maximum of 28.8×108 l-1 in Tvillingvatnet and 23.6×108 l-1 in Lake OS. Ciliated protozoan and rotifer diversity in the plankton was low.